2012
DOI: 10.1155/2012/628406
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Bone Metabolism in Oral Cavity

Abstract: Throughout life, bone tissue undergoes a continuous process of resorption and formation. Melatonin, with its antioxidant properties and its ability to detoxify free radicals, as suggested by Conconi et al. (2000) may interfere in the osteoclast function and thereby inhibit bone resorption, as suggested by Schroeder et al. (1981). Inhibition of bone resorption may be enhanced by a reaction of indoleamine in osteoclastogenesis. That it has been observed melatonin, at pharmacological doses, decrease bone mass res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Consequently, age-related disorders, such as osteoporosis and deficient implant osseointegration issues, are suspected to be affected by the decrease in MEL secretion. In fact, MEL has been demonstrated to affect bone metabolism through both bone anabolic as well as antiresorptive effects, as reviewed in [Cardinali et al, 2003;López-Martínez et al, 2012;Liu et al, 2013]. Moreover, many authors have suggested potential beneficial effects of MEL on periodontal regeneration or in dental implantology [Carrillo-Vico et al, 2005;Cutando et al, 2007;Gomez-Moreno et al, 2010;Gómez-Florit et al, 2013].…”
mentioning
confidence: 99%
“…Consequently, age-related disorders, such as osteoporosis and deficient implant osseointegration issues, are suspected to be affected by the decrease in MEL secretion. In fact, MEL has been demonstrated to affect bone metabolism through both bone anabolic as well as antiresorptive effects, as reviewed in [Cardinali et al, 2003;López-Martínez et al, 2012;Liu et al, 2013]. Moreover, many authors have suggested potential beneficial effects of MEL on periodontal regeneration or in dental implantology [Carrillo-Vico et al, 2005;Cutando et al, 2007;Gomez-Moreno et al, 2010;Gómez-Florit et al, 2013].…”
mentioning
confidence: 99%
“…In all of the components (except enamel), the organic component is comprised of 90% (by weight) of type I collagen fibers and 10% of non-collagenous proteins. The inorganic phase is constituted by small crystals of a mineral alkaline character, hydroxyapatite (HA) [Ca 10 (PO 4 ) 6 (OH) 2 ] [18]. …”
Section: Bone and Toothmentioning
confidence: 99%
“…There are four distinct phases to this process: activation, resorption, reversal, and formation with resorption and formation taking place via osteoclasts and osteoblasts, respectively [14]. Initially, osteoclast precursors are attracted to a particular area of bone surface, then differentiation into osteoclast, which is responsible to bone resorption by acidification and proteolytic digestion [18]. In the reversal phase, bone resorption transitions into bone formation, and osteoblast precursors are recruited to proliferate and differentiate into osteoblasts that invade the resorption area and begin to form new bone by secreting osteoid, which is eventually mineralized [14].…”
Section: Melatonin and Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Bone structures undergo a continuous remodeling process of resorption and formation via osteoclasts and osteoblasts, which are responsible for destroying the old bone architecture and building a new one respectively (Lopez-Martinez et al 2012). Osteoporosis, a bone disease characterized by low bone mass and micro-architectural deterioration, is caused by dysfunction of both cell types (Sanchez-Barcelo et al 2010).…”
Section: Introductionmentioning
confidence: 99%